Generalized Hyers-Ulam Type Stability of the $2k$-Variables Quadratic $β$-Functional Inequalities And Function in $γ$-Homogeneous Normed Space - Ly Van An (International Journal of Mathematics And its Applications, 2021)
In this paper, we study to solve two quadratic $β$-functional inequalities with $2k$-variables in $γ$-homogeneous complex Banach spaces and prove the Hyers-Ulam stability of quadratic $β$-functional equations associated two the quadratic $β$-functional inequalities in $γ$-homogeneous complex Banach spaces. We will show that the solutions of the first and second inequalities are quadratic mappings.